2006
DOI: 10.1128/mcb.01515-05
|View full text |Cite
|
Sign up to set email alerts
|

Anaplastic Lymphoma Kinase Is a Dependence Receptor Whose Proapoptotic Functions Are Activated by Caspase Cleavage

Abstract: Anaplastic lymphoma kinase (ALK) is a receptor tyrosine kinase, initially discovered as part of the NPM-ALK fusion protein, resulting from the t(2;5) translocation that is frequently associated with anaplastic large-cell lymphomas. The native ALK protein is normally expressed in the developing and, at a weaker level, adult nervous system. We recently demonstrated that the oncogenic, constitutively kinase-activated NPM-ALK protein was antiapoptotic when expressed in Jurkat lymphoblastic cells treated with cytot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
92
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(97 citation statements)
references
References 46 publications
3
92
1
1
Order By: Relevance
“…The native full-length ALK receptor is mainly expressed in discrete regions of the developing central and peripheral nervous system (Iwahara et al, 1997). Mourali et al (2006) forced ALK expression in cells of lymphoid and neuronal origin to investigate wild-type ALK functions. They observed that ALK enhanced or triggered apoptosis in these cells and that treatment with agonist antibodies mimicking ALK ligand prevented cell death induction (Mourali et al, 2006).…”
Section: Dependence Receptors: a Short Historymentioning
confidence: 99%
See 3 more Smart Citations
“…The native full-length ALK receptor is mainly expressed in discrete regions of the developing central and peripheral nervous system (Iwahara et al, 1997). Mourali et al (2006) forced ALK expression in cells of lymphoid and neuronal origin to investigate wild-type ALK functions. They observed that ALK enhanced or triggered apoptosis in these cells and that treatment with agonist antibodies mimicking ALK ligand prevented cell death induction (Mourali et al, 2006).…”
Section: Dependence Receptors: a Short Historymentioning
confidence: 99%
“…Mourali et al (2006) forced ALK expression in cells of lymphoid and neuronal origin to investigate wild-type ALK functions. They observed that ALK enhanced or triggered apoptosis in these cells and that treatment with agonist antibodies mimicking ALK ligand prevented cell death induction (Mourali et al, 2006).…”
Section: Dependence Receptors: a Short Historymentioning
confidence: 99%
See 2 more Smart Citations
“…ALK is functionally important in embryonic development [3] and in determination of cell survival and cell fate [4]. However, ALK was originally discovered when it was found that the chimeric N-terminal nucleophosmin (NPM) domain/cytoplasmic (catalytic) ALK domain fusion protein (NPM-ALK) is the oncoprotein underlying the pathogenesis of anaplastic large cell lymphomas (ALCL) [5,6].…”
Section: Introductionmentioning
confidence: 99%